KEBIJAKAN MONETER DAN BANK DALAM PERSPEKTIF EKONOMI SYARIAH DI INDONESIA - Imam Mawardi (STIE Bakti Bangsa Pamekasan, 2023)
This study aims to find out important questions about monetary policy, namely whether monetary policy influences output. Monetaryists argue that money is the most important factor affecting output, such as government spending.The methodology in this study, namely library research, this research approach uses normative research, with the type of library research. While the technique of data collection by conducting research on various relevant literature from this discussion through the study of books, journals, websites and expert opinion indirectly.The results of this study are that Islamic banks play an important role in transmitting monetary policy to the real sector. Then their study shows that monetary policy supports the real effect. Monetary policies funded by conventional banks and Islamic banks play a very important role in the economic sectors in manufacturing, hotels, business services, trade, restaurants, construction, social services, agriculture and construction. If the rupiah depreciates against the US dollar, the demand for loans by manufacturing companies will certainly fall. The central bank will not allow the rupiah to depreciate further, because this event will affect other companies, which have different characteristics. To avoid all of this, the central bank will raise interest rates by policy, so as to encourage consumption and investment. The goal is to strengthen the rupiah against the US dollar. Keyword: Monetary Policy, Conventional and Sharia, inflation.